Factors affecting changes in eating behavior of Japanese medalists in judo at the Rio Olympics - Oshiba, Y.; Seino, J.; Ogata, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2020)
This research focused on three Japanese medalists in judo at the Rio Olympics as subjects, and its purpose was to clarify factors affecting changes in eating behavior of subjects with high rarity. Subjects were given semi-structured interviews, and analysis of the obtained data was carried out using a modified grounded theory approach. The following points were indicated as results: 1) Carrying out reflection and introspection had the effect on strengthening intrinsic motivation, and led to acquisition of indicators of eating behavior with high autonomy. 2) Nutritionist guidance and involvement were present as external factors, and that autonomy support of nutritionists affected changes in athlete eating behavior. 3) Meals prepared by the athletes' mothers while in elementary and junior high schools had some effect on subsequent changes in eating behavior. The above points suggest that a guidance environment enabling autonomy support is needed, even in the area of eating behavior.